Vulgarization of Language as Context for the Socialization of Children and Adolescents/ Wulgaryzacja języka jako kontekst socjalizacji dzieci i młodzieży - Pankowska, Dorota; Bieganowska-Skóra, Anna (Przegląd Badań Edukacyjnych (Educational Studies Review), 2018)
The more and more intensive process of language vulgarisation has for a long time been a subject of linguistic research, but it has rarely been reflected on by pedagogues. The authors of this article conduct a study of language in the context of the socialisation process. Basing on their own and other authors’ research they describe the children’s and adolescents’ language environment abounding in vulgarisms, and reflect on possible effects of its influence on different spheres of young people’s development. The immediate result, confirmed by empirical material, is a considerable intensification of the vulgarisation of the young generation’s language, which has its consequences for cognitive, emotional, psychosexual and moral development of children and adolescents (e.g. lower language competences, lack of discernment in their own emotions, negative attitude to other people, increased aggressiveness or a vulgar image of sexuality). However, the conclusions mentioned above are considered on the basis of general knowledge about psychological rules and mechanisms of growing personalities, and require verification through empirical research.